TẠO MÀNG PHỦ SILICA LAI VÔ CƠ - HỮU CƠ TRÊN NỀN HỢP KIM NHÔM - Hà, Hữu Sơn; Nguyễn, Văn Vinh; Nguyễn, Thị Yến; Nguyễn, Đức Hùng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
PREPARATION OF ORGANIC INORGANIC HYBRID SILICA FILMS ON ALUMINUM ALLOY BY DEPOSITION METHODSIn this work, the hybrid silica coatings on the aluminum alloy have been produced by two methods: dip coating and electrophoretic deposition. The protective behavior against corrosion of the produced films was studied through polarization curves measurements in aggressive media (3,5% NaCl solution). The corrosion resistance of coatings produced by dipping is much lower than by electrophoretic deposition. The composition and morphology of coatings were also investigated at different heat treating temperatures. The results showed that the heat treatment of the ormosil coatings after electrophoretic deposition is necessary at the temperature not higher than 400oC.